2014
DOI: 10.1371/journal.pone.0113801
|View full text |Cite
|
Sign up to set email alerts
|

IGF-1 Promotes Brn-4 Expression and Neuronal Differentiation of Neural Stem Cells via the PI3K/Akt Pathway

Abstract: Our previous studies indicated that transcription factor Brn-4 is upregulated in the surgically denervated hippocampus in vivo, promoting neuronal differentiation of hippocampal neural stem cells (NSCs) in vitro. The molecules mediating Brn-4 upregulation in the denervated hippocampus remain unknown. In this study we examined the levels of insulin-like growth factor-1 (IGF-1) in hippocampus following denervation. Surgical denervation led to a significant increase in IGF-1 expression in vivo. We also report tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 56 publications
1
36
0
Order By: Relevance
“…NSCs were prepared from the hippocampus of Sprague–Dawley (SD) rats at embryonic days 14 (E14), which were obtained from Laboratory Animal Centre of Cheeloo College of Medicine, Shandong University. The protocol was the same as that described previously (Zhang et al, ). In brief, rats were anesthetized with chloral hydrate (2‐ml/kg body weight), followed by a quick dissection of hippocampus under sterile condition.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…NSCs were prepared from the hippocampus of Sprague–Dawley (SD) rats at embryonic days 14 (E14), which were obtained from Laboratory Animal Centre of Cheeloo College of Medicine, Shandong University. The protocol was the same as that described previously (Zhang et al, ). In brief, rats were anesthetized with chloral hydrate (2‐ml/kg body weight), followed by a quick dissection of hippocampus under sterile condition.…”
Section: Methodsmentioning
confidence: 99%
“…The protocol was the same as that described previously (Zhang et al, 2014). In brief, rats were anesthetized with chloral hydrate (2ml/kg body weight), followed by a quick dissection of hippocampus under sterile condition.…”
Section: Primary Cell Culturementioning
confidence: 99%
“…However, the outcome of the therapeutic effects of MSCs on neurogenesis and recovery of brain function is not sufficient, and remains to be further improved. Brn-4 is a transcription factor that plays a critical role in neuronal development [18,19,20,21], whereas the effects of Brn-4 overexpression in transplanted MSCs on AD are unknown. Therefore, increasing the levels of Brn-4 in MSCs may be examined to evaluate its effects on the outcome of MSC transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…The extracts of the denervated hippocampus following fimbria fornix transection improved the survival, migration, and neuronal differentiation of NSCs compared with the extracts of normal hippocampus (Zhang et al, ). We also found that IGF‐1 could upregulate Brn4 by activating the PI3K/Akt signaling pathway, which in turn enhances the differentiation of NSCs into neurons (Zhang et al, ). These results suggest that Brn4 plays an important role in the process of NSC differentiation into neurons, and IGF‐1 controls its expression.…”
Section: Introductionmentioning
confidence: 88%